Implementasi Sistem Monitoring Jaringan dan Server Menggunakan Zabbix yang Terintegrasi dengan Grafana dan Telegram - Muhammad Aliyul Husna; Perani Rosyani (JURIKOM (Jurnal Riset Komputer), 2021)
The network administrator is a person who is responsible for managing computer networks. One of the duties of a network administrator is network monitoring because errors on the server and services running on the server cannot be known when it happened. This can be difficult if the administrator is far from a surveillance center. A network Monitoring System is a system that helps Network Administrators in supervising and managing computer networks that exist in an agency. By using the system that will be implemented in this research, the computer network monitoring process can be monitored remotely, anywhere and anytime as long as it is connected to the Internet network. With this Network Monitoring System, it is hoped that in the long term PT Cyber Network Indonesia can implement an integrated and well-monitored Internet network system. Test results using Network Monitoring Zabbix, generate real-time data regarding bandwidth usage, problem logs and resource availability.